A SPECTRUM AWARE CLUSTER-BASED ARCHITECTURE FOR COGNITIVE RADIO AD-HOC NETWORK - Nafees Mansoor, 1983-, author; A.K.M. Muzahidul Islam, Dr., supervisor; Sabariah Baharun, Assoc.Prof.Dr., supervisor; Institut Teknologi Antarabangsa Malaysia-Jepun (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016